EFEKTIVITAS SUHU TERHADAP PERTUMBUHAN BAKTERI Bacillus cereus STRAIN IMB-10 DALAM MENDEGRADASI BAHAN BAKAR SOLAR SEBAGAI SUMBER RANCANGAN MODUL PEMBELAJARAN BIOLOGI SMA - Dian Munawarah; Irda Sayuti; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the effectiveness of temperature on the growth of Bacteria Bacillus cereus strain IMB-10 in degrading diesel fuel. This research was carried out in the UR FKIP PMIPA laboratory to determine how the effectiveness of temperature on the growth of Bacteria Bacillus cereus strain IMB-10 in degrading diesel fuel and measuring the level of degradation of TPH (Total Petroleum Hydrocarbons) for diesel fuel which was carried out at the Faculty of Civil and Environmental Engineering ITB. The research was conducted in November 2019 - June 2020. This research was descriptive with an experimental method, the research design used was a completely randomized design consisting of 4 treatments and 4 repetitions, the media used was SMSS media with different temperature variations, namely temperatures of 310C, 340C , 370C and 400C then added 5% diesel fuel and bacterial isolate Bacillus cereus strain IMB-10. The parameters tested were Optical Dencity (turbidity level) growth of Bacillus cereus Strain IMB-10 spectrophotometer and measurement of the degradation rate (Total Petroleum Hydrocarbons) TPH which consisted of 2 steps, namely measuring the initial TPH and final TPH using the gravimetric method. Based on the results of the study, the temperature of 340C is an effective temperature for the growth of the bacteria Bacillus cereus Strain IMB-10 with the highest OD value on day 5 of 3.6 A and a reduction in the level of diesel fuel degradation by 35.91%. The potential results are used as a source for the design of the KD 3.5 and KI 3.5 biology learning modulesKey Words: Temperature effectiveness, Bacteria Bacillus cereus Strain IMB-10,degradation, diesel fuel, modules